Self Disclosure Pasangan Ta’aruf: Perspektif Komunikasi Interpersonal - Musrifah Musrifah (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2017)
This study describes the dimensions of self-disclosure in conversation topics husband and wife through taaruf in the first year of marriage. Taaruf is the choice for people who do not want dating. Taaruf is a brief introduction of men and women who intend to marry following the guidance of Islam. Dimensions of self disclosure includes breadth, depth, valence, frequency, and duration. The results of research showed that married couples through taaruf undertaken efforts to develop interpersonal relationships through the stages of contact, intimacy, involvement and openness in which intensifitas interaction begins after marriage. Process of coming together at the couple through the stages of initiating taaruf-bonding-experimenting-Integrating-intensifying. Self disclosure on topics of husband and wife talk show of the variability in each pair. This study provides a new discourse that enrich science communication research. Especially research related interpersonal relationships and interpersonal communication. As a research-laden communication aspects of psychology, the study also opens up opportunities for the emergence of research from other disciplines, because the phenomenon of marital communication via taaruf can be viewed from the sociology of science communication, social psychology and so forth.